Mechanical circulatory support and intravascular lithotripsy in high-risk patients undergoing percutaneous coronary intervention and transcatheter aortic valve replacement: a case series. Issue 12 (7th December 2021) - Marchese, Alfredo; Tarantini, Giuseppe; Tito, Antonio; Margari, Vito; Resta, Fabrizio; Dhojniku, Ilir; Paparella, Domenico; Speziale, Giuseppe
Abstract: Background: Patients undergoing transcatheter aortic valve replacement (TAVR) usually have multiple comorbidities, such as severely impaired left ventricular function (LVF) and heavily calcified coronary lesions. When they undergo pre-TAVR high-risk percutaneous coronary interventions (HR-PCIs) for severely calcified left main (LM) lesions, potential life-threatening intra-procedural complications associated with the different techniques available to treat calcified lesions can arise. In this setting, mechanical circulatory support proves its usefulness. However, the choice of device can be troublesome. Case summary: We report two clinical scenarios of intravascular lithotripsy (IVL) for the treatment of heavily calcified LM coronary lesions, wherein peripheral veno-arterial extracorporeal membrane oxygenation (VA-ECMO), alone or combined with an intra-aortic balloon pump (IABP), were used as an upfront strategy to support the procedure. The use of these techniques was particularly effective during multi-vessel HR-PCIs and TAVR, and no complications occurred, which suggested their safety. Discussion: These cases provide multiple insights into the strategy of using IVL + VA-ECMO, alone or with IABP, to treat heavily calcified LM coronary lesions in patients with severely compromised LVF undergoing TAVR. IVL safely and effectively overcame shortcomings related to other plaque ablation techniques, and VA-ECMO proved to be effective when facing the combination of high-risk coronary and valve interventions.